Unlinking chromosome catenanes in vivo by site-specific recombination. - Grainge, I; Bregu, M; Vazquez, M; Sivanathan, V; Ip, S; Sherratt, D (2007)
A challenge for chromosome segregation in all domains of life is the formation of catenated progeny chromosomes, which arise during replication as a consequence of the interwound strands of the DNA double helix. Topoisomerases play a key role in DNA unlinking both during and at the completion of replication. Here we report that chromosome unlinking can instead be accomplished by multiple rounds of site-specific recombination. We show that step-wise, site-specific recombination by XerCD-dif or Cre-loxP can unlink bacterial chromosomes in vivo, in reactions that require KOPS-guided DNA translocation by FtsK. Furthermore, we show that overexpression of a cytoplasmic FtsK derivative is sufficient to allow chromosome unlinking by XerCD-dif recombination when either subunit of TopoIV is inactivated. We conclude that FtsK acts in vivo to simplify chromosomal topology as Xer recombination interconverts monomeric and dimeric chromosomes.